1976
DOI: 10.1203/00006450-197601000-00004
|View full text |Cite
|
Sign up to set email alerts
|

γ-Glutamyltranspeptidase in the Rat Liver after Portacaval Shunt

Abstract: Extractweight have been re~orted (I. 15). The metabolism of bile salts and y-Glutamyltranspeptidase (GGTP) activity was studied in livers of rats submitted to an end-to-side portacaval shunt (PCS) and in developing animals. To correlate the evolution of the enzymatic activity measured in vitro, histochemical techniques were used to localize enzyme activity in liver tissue. The GGTP activity in the adult rats was low and amounted to 2.0 =k 0.1 pmol/min/g. During fetal development the enzyme activity rose beginn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1977
1977
1994
1994

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…As a direct consequence of portal blood diversion liver shrinkage takes place, the size after 10 days remaining constant (8,10,17). The increased DNA content per unit liver weight in the PCS group and the control group with the same dietary intake compared to unoperated and sham-operated controls show that more cells are present per volume of liver weight.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…As a direct consequence of portal blood diversion liver shrinkage takes place, the size after 10 days remaining constant (8,10,17). The increased DNA content per unit liver weight in the PCS group and the control group with the same dietary intake compared to unoperated and sham-operated controls show that more cells are present per volume of liver weight.…”
Section: Discussionmentioning
confidence: 83%
“…A minor fraction of the circulatalone as has been suggested up to now (10), but may also be connected to the reduced food intake of these animals. It is not clear, however, whether the elevated amount of DNA is due to an augmented production of new but smaller and younger hepatocytes, or to shrinkage of the prevailing cells, or both.…”
Section: Discussionmentioning
confidence: 99%
“…Weinbren (18) has demonstrated that portacaval shunting in rats can produce nodularity in the liver. Colombo et al (19) have shown that the liver parenchyma becomes positive for GGT after portacaval shunting but the enzymes appear primarily in the periportal zones rather than randomly in small foci of hepatocytes as seen in the model described by Solt et al (1). It seems, therefore, that the GGT positivity seen after shunting is in response to physiological modulation rather than a phenotypic marker for preneoplasia.…”
Section: Discussionmentioning
confidence: 98%
“…Whether there exists a common denominator to the elevation of hepatic GGT in PCS and in chemically induced hepatocarcinogenesis is not known. The hypothesis that both procedures represent the reacquisition of a fetal, biochemical feature which is normally repressed in the adult is therefore difficult to prove or disprove (8,9). Everts et al believe that after PCS, the distribution of GGT is periportal, whereas after the administration of chemical carcinogens the enzyme is mostly concentrated in the midzonal areas.…”
Section: Commentsmentioning
confidence: 99%